11.1: Invited Paper: Narrow‐Band Phosphors for Next Generation MiniLED and MicroLED Displays. (26th August 2021) - Murphy, James; Camardello, Samuel; Doherty, Mark; Liu, Jerry; Smigelski, Paul; Setlur, Anant
Abstract : Both phosphors and quantum dots are currently used in liquid crystal displays (LCDs), with GE's KSF narrow red phosphor demonstrating the best possible red color point, reliability, and efficiency. Next generation miniLED and microLED based displays require excellent color quality (gamut) and high brightness which will require color conversion materials with high EQE and narrow emission peaks. Here we describe recent advancements in narrow‐band phosphors which are being implemented in next‐generation miniLED displays, and being considered for enabling full‐color microLED displays of thefuture due to their excellent optical performance and robust nature.